2007
DOI: 10.2146/ajhp070080
|View full text |Cite
|
Sign up to set email alerts
|

Telavancin: A novel lipoglycopeptide antimicrobial agent

Abstract: Telavancin is a promising new agent for gram-positive infections and may offer an alternative to vancomycin for MRSA-associated infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…The lipophilic moiety of telavancin interacts directly with the bacterial cell membrane, resulting in depolarisation and increased permeability of the cell membrane. As shown in this study, telavancin MICs have previously been reported to be two to eight times lower than corresponding vancomycin MICs [10].…”
Section: Discussionsupporting
confidence: 60%
“…The lipophilic moiety of telavancin interacts directly with the bacterial cell membrane, resulting in depolarisation and increased permeability of the cell membrane. As shown in this study, telavancin MICs have previously been reported to be two to eight times lower than corresponding vancomycin MICs [10].…”
Section: Discussionsupporting
confidence: 60%
“…Animal model data suggest efficacy in the treatment of bacteremia, endocarditis, meningitis, and pneumonia caused by gram-positive pathogens (1,16,19,20,28). Our findings suggest that future use of telavancin holds promise in treating infections caused by biofilm-producing staphylococci and enterococci and that it should be further evaluated for the treatment of biofilm-re-FIG.…”
mentioning
confidence: 84%
“…Telavancin possesses a second mechanism of action that causes rapid depolarization and loss of the functional integrity of the bacterial membrane (1,12). These two mechanisms of action may be implicated in the lower range of methicillin (meticillin)-resistant Staphylococcus aureus (MRSA) MICs observed with telavancin (MIC range, 0.06 to 1.0 g/ml) compared to vancomycin (MIC range, 0.5 to 2 g/ml) (8,13).…”
mentioning
confidence: 99%
“…114 Although the telavancin MIC 90 was elevated against VRE, it was appreciably lower than that observed with vancomycin (MIC 90 > 256 µg/mL). 115 However, it is unknown if these differences in MIC will result in any clinical benefit because most vancomycin-resistant E faecium isolates possess the VanA gene. Its place in therapy is likely to be limited, and no clinical data in VRE bacteremia are available.…”
Section: Telavancinmentioning
confidence: 99%